Long-term disease-free survival of a patient diagnosed with peri-ampullary carcinoma treated with adjunct Ayurvedic treatment – A case report - Sadanand Sardeshmukh; Vineeta Deshmukh; Swapna Kulkarni; Vasanti Godse; Vinita Awalkanthe; Shreenivas Datar; Shweta Gujar; Sandeep Chavan (Journal of Ayurveda and Integrative Medicine)
This is a case of a female Indian patient diagnosed as Peri-Ampullary Carcinoma, with metastasis to regional lymph nodes, and reported 5-year disease free survival rate of 20–50%, treated with integration of personalized Ayurvedic treatment along with conventional treatments viz., surgery and adjuvant chemotherapy.The patient was diagnosed with adenocarcinoma through biopsy from the ampulla of Vater during registration at our Centre in May 2010. She had yet to start her conventional treatment which was advised viz., surgery and adjuvant chemotherapy. In June 2010, she underwent Whipple's resection. Histopathology report showed moderately differentiated adenocarcinoma of the periampullary region with metastasis to regional lymph nodes — Completely resected (R0). According to TNM (Tumor Node Metastasis) Staging System as per Union for International Cancer Control (UICC- 6th edition) patient was staged as pT3N1- Stage IIB. After completion of conventional treatment (surgery and chemotherapy) in October 2010, she continued with Ayurvedic treatment and follow-ups till date. Her tumour marker CA19.9 and sonography – abdomen, pelvis after 12 years revealed no evidence of malignancy. In May 2017, she was hospitalized for hematemesis and melena, diagnosed as mild gastritis with clean base ulcers at the surgical anastomosed (Gastrojejunostomy) site. She was treated accordingly with Ayurvedic medicines and her follow-up report showed the resolution of ulcers by September 2017. In May 2014, her mildly raised blood sugar (Fasting 138 mg/dL; Post-Prandial 146 mg/dL) was managed by a healthy lifestyle but in 2019, her blood glucose levels were moderately raised (Fasting 153 mg/dL, Post-Prandial 187 mg/dL) hence she was started on oral hypoglycemics which are continued till date.Though the pancreaticobiliary subtype is associated with poor prognosis, it was possible to achieve 12 years and 6 months of disease-free survival with adjunct Oral Ayurvedic Medicines (OAM) possessing antioxidant, immune-modulatory, anti-cancer, and hepato-protective action. She could tolerate chemotherapy with minimal side effects. Her quality of life improved. Her blood sugar levels have been maintained by lifestyle changes and oral hypoglycemics.